PENGARUH RETAIL MIX TERHADAP KEPUASAN PELANGGAN PADA UNAGI BALI HANDYCRAFT AND SOUVENIR GALLERY - Gentha Maheza, Vincentius; Wulandari Kusumadewi, Ni Made (E-Jurnal Manajemen, 2015)
The existence of modern retail in particular retail businesses increasingly penetrated into the daily activities of the community. The development of higher retail business and competitive force employers retail business to be able to determine the right strategy in order to survive in the competition and gain customer satisfaction, one of them by applying a mix of retail strategy consisting of price, merchandise, services, store locations, promotions, and store atmosphere. The number of samples was 168 respondents, with purposive sampling method. This study uses multiple linear regression analysis techniques and based on the results of the analysis found that the retail mix simultaneously significant positive effect on customer satisfaction.
Keywords: retail; retail mix; customer satisfaction